(untitled) (Journal of Hama University, 2020)
Formalin fumigation is routinely used to disinfect hatching eggs in farms of broiler breeders , broiler and hatchery. Immersing of hatching eggs in various antiseptic solutions has not been used as a means of disinfecting hatching eggs. The study was conducted to determine the effect of different methods of disinfection on hatching and mortality (early, middle, late). This study was conducted on 1080 hatching eggs from clean nests. These eggs were disinfected by formaldehyde evaporation with permanganate Potassium (formal) or formaldehyde in water or by formalin 1% or peracetic acid 3%. It was found that the hatching rate and the mortality rate of the embryos were not affected by the different disinfection treatments, but they were better for the hatching eggs that were disinfected with formalin, which was immersed in a solution peracetic acid. The study concluded that the decontamination of hatching eggs by immersing in a solution of peracetic acid may be a substitute for formalin which is currently used.